2008
DOI: 10.1063/1.2888957
|View full text |Cite
|
Sign up to set email alerts
|

Application of ion scattering spectroscopy to measurement of surface potential of MgO thin film under ion irradiation

Abstract: An experimental approach was proposed for the measurement of the surface potential (SP) induced on an insulator surface during ion irradiation by ion scattering spectroscopy (ISS). The resultant ISS spectra obtained for a MgO thin film of 600nm thickness on a Si substrate under 950eV He+ irradiation revealed that the surface is positively charged by approximately 230V. In addition, the onset energy of a secondary ion peak indicated a SP of approximately 205V. The present results confirmed that ISS is an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…Therefore, γ is one of the most important parameters of the MgO protective layer for improving the discharge characteristics, 1,6 and the IISE phenomenon in MgO films has been intensively studied. [7][8][9][10][11][12][13][14][15] The magnitude of γ is strongly influenced by the MgO film electronic structure. It has been reported that γ is closely related to defect states 16 and γ increases as the number of surface defect states in MgO increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, γ is one of the most important parameters of the MgO protective layer for improving the discharge characteristics, 1,6 and the IISE phenomenon in MgO films has been intensively studied. [7][8][9][10][11][12][13][14][15] The magnitude of γ is strongly influenced by the MgO film electronic structure. It has been reported that γ is closely related to defect states 16 and γ increases as the number of surface defect states in MgO increases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] To display dynamic images using AC-PDPs, a firing voltage is applied to the electrodes to initiate discharge. Then, ultraviolet photons emitted from the plasma are absorbed in phosphors, and visible photons are generated.…”
Section: Introductionmentioning
confidence: 99%
“…The base pressure of the apparatus was 7 ϫ 10 −8 Pa. 19 The main purpose of attaching the Ta plate is not to measure ␥ using the Ta plate as the collector electrode of secondary electrons but to reduce the effects of the distortion of the electric field in the ISS measurement. [20][21][22] The samples were MgO films deposited on a Si substrate by electron beam deposition.…”
Section: A Experimental Conditionsmentioning
confidence: 99%
“…In our previous study, 19 we proposed a new technique for measuring the surface potential under positive ion irradiation by ion scattering spectroscopy ͑ISS͒, which is a widely used technique for analyzing the composition of the outermost surface layer. The application of ISS enables the measurement of surface potential without applying a bias voltage to the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Более изучены механизмы зарядки диэлектриков под воздействием электронных пучков средних энергий [7], причем как исходных, так и предварительно облученных ионами [8][9][10]. Что касается конкретной ионной зарядки поверхности диэлектрика, то большая часть немногочисленных публикаций посвящена зарядке тонких пленочных мишеней [11][12][13][14][15].…”
Section: Introductionunclassified